The Economic Basis of the Model of Traditional Montenegrin Masculinity - Branko Banović (University of Belgrade, 2016)
The model of traditional Montenegrin masculinity is inseparable from the social formations that have contributed to its creation, hence the need for its more thorough economic, social and historical contextualization. It is particularly important to distinguish the two components of the model of traditional Montenegrin masculinity, which tend to be intertwined and are therefore difficult to separate. The first concerns the gender roles assigned to men and women in an economy based on livestock raising, warfare, and raiding, while the other concerns the concept of gender roles shaped by fictional, ethnological and historical narratives. The paper attempts to problematize the economic basis of the model of traditional Montenegrin masculinity in the context of a semi-nomadic livestock raising economy and a clan’s collective property.